â€œKULIAH versus ORGANISASIâ€ STUDI KASUS MENGENAI STRATEGI BELAJAR PADA MAHASISWA YANG AKTIF DALAM ORGANISASI MAHASISWA PECINTA ALAM UNIVERSITAS DIPONEGORO - Caesari, Yasinta Karina; Listiara, Anita (Faculty of Psychology, Diponegoro University, 2013)
The aim of this research is to describe about students who active in W organization of Diponegoro University concerned with their role and status as student and member of its organization. This research had done to two subjects of W organization members. This research uses a case study qualitative research method and using descriptive data analizing technique. The result of research shows that learning strategy that use by those subjects could be categorized as surface learning approaches. Those subjects would like and easy to do the organization assignment although they delay assignment conveniently than academic assignment. Those subjects prefer to do assignment close to the deadline and often cheat their friendsâ€™ assignment. The attendances of subjects in learning activities were less and they often order to their friend to fill the attendance list. Academic achievement of those subjects has decrease, expecially in the third grade. W organization has important to those subjects, because they get some advantages, include new environment, learning and refreshing environment, and expand the communication network.Keywords: Learning stratgey, students, natural loversâ€™ organization